Relative Efficacy of Intra-articular Injections in the Treatment of Knee Osteoarthritis: A Systematic Review and Network Meta-analysis - Singh, Harsh; Knapik, Derrick M; Polce, Evan M; Eikani, Carlo K; Bjornstad, Amanda H; Gursoy, Safa; Perry, Allison K; Westrick, Jennifer C; Yanke, Adam B; Verma, Nikhil N; Cole, Brian J; Chahla, Jorge A (The American journal of sports medicine, 2022)
In younger patients and those without severe degenerative changes, the efficacy of intra-articular (IA) injections as a nonoperative modality for treating symptomatic knee osteoarthritis (OA)-related pain while maintaining function has become a subject of increasing interest. To assess and compare the efficacy of different IA injections used for the treatment of knee OA, including hyaluronic acid (HA), corticosteroids (CS), platelet-rich plasma (PRP), and plasma rich in growth factors (PRGF), with a minimum 6-month patient follow-up. Meta-analysis of randomized controlled trials; Level of evidence, 1. A systematic review was performed according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines using the following databases: PubMed/MEDLINE, Scopus, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and Google Scholar. Mean or mean change from baseline and standard deviation for outcome scores regarding pain and function were recorded at the 6-month follow-up and converted to either a 0 to 100 visual analog scale score for pain or a 0 to 100 Western Ontario and McMaster Universities Osteoarthritis Index score for function. A frequentist network meta-analysis model was developed to compare the effects of HA, CS, PRP, PRGF, and placebo on patient-reported outcomes. All IA treatments except CS were found to result in a statistically significant improvement in outcomes when compared with placebo. PRP demonstrated a clinically meaningful difference in function-related improvement when compared with CS and placebo due to large effect sizes. Studies evaluating outcomes of PRGF reported significant improvement when compared with placebo due to large effect sizes, whereas a potential clinically significant difference was detected in the same comparison parameters in pain evaluation. With regard to improvements in pain, function, and both combined, PRP was found to possess the highest probability of efficacy, followed by PRGF, HA, CS, and placebo. PRP yielded improved outcomes when compared with PRGF, HA, CS, and placebo for the treatment of symptomatic knee OA at a minimum 6-month follow-up. Further investigations evaluating different IA and other nonoperative treatment options for patients with knee OA are warranted to better understand the true clinical efficacy and long-term outcomes of nonsurgical OA management.